Regional Differences in Thrombectomy Rates : Secondary use of Billing Codes in the MIRACUM (Medical Informatics for Research and Care in University Medicine) Consortium - Haverkamp, Christian; Ganslandt, Thomas; Horki, Petar; Boeker, Martin; Dörfler, Arnd; Schwab, Stefan; Berkefeld, Joachim; Pfeilschifter, Waltraud; Niesen, Wolf-Dirk; Egger, Karl; Kaps, Manfred; Brockmann, Marc A.; et al. (Clinical Neuroradiology, 2018)
Mechanical thrombectomy, in addition to intravenous (i.v.) thrombolysis is recommended for treatment of acute stroke in patients with large vessel occlusions (LVO) in the anterior circulation up to 6 h after symptom onset. We compared thrombectomy rates of eight university hospitals of the MIRACUM consortium to analyze the implementation of this guideline in clinical routine.Anonymized billing data in a standardized format were loaded into a local i2b2 data warehouse by applying already existing extract, transform and load (ETL) routines. A locally executed uniform SQL (structured query language) query delivered aggregated site data for all inpatients with a discharge diagnosis of ischemic stroke (ICD-10 I63) containing counts for type of acute treatment, type of admission and age groups, which were centrally analyzed with R.From 2014 to 2016, the thrombectomy rate almost doubled from a mean of 4.7% to 9.6%, although significant differences between centers exist (range in 2016: 5.8-17%). The number of drip-and-ship procedures increased in 3 out of 8 centers. There was no evidence for a decrease in thrombectomy rates during weekends/holiday or among patients older than 80 years, but this age group is more likely to receive i.v. recombinant tissue plasminogen activator (rtPA).The observed increase of thrombectomy rates and drip-and-ship procedures without a significant difference between weekdays and weekends or patients of different ages is substantiating a rapid implementation of stroke guidelines within the analyzed neurovascular centers. The prototype of the MIRACUM Data Integration Center already contributes to health services research in Germany.
EVALuna2:196